2017
DOI: 10.21608/ejar.2017.148933
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a Thermostable Bovine Ephemeral Fever Virus Vaccine Inactivated on the Time of Use

Abstract: he herein study was devoted to overcome the obstacles dealing with the utilization of the live attenuated Bovine Ephemeral Fever (BEF) vaccine viz, the cold chain and the undesirable post-vaccinal reaction. Methylglucoside-sucrose (MS) was proved to be an excellent stabilizer for BEF thermostable vaccine. The permissible titer of the lyophilized MS-BEF thermostable vaccine was achieved even after 6 months at 25°C, 3 months at 37°C and 20 days at 45°C. The study revealed that freeze-dried MS-BEF thermostable va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…If we look back at recent and past history, our literature search highlights that the freeze-drying process is a valuable method to obtain vaccine thermostability [47,49,50,52,[65][66][67]70,74,76,79,85]. An improved freeze-drying process was used to develop a thermostable Rinderpest vaccine (Thermovax), which was an essential tool for eradicating the disease in remote pastoral areas [127].…”
Section: Summary Of Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…If we look back at recent and past history, our literature search highlights that the freeze-drying process is a valuable method to obtain vaccine thermostability [47,49,50,52,[65][66][67]70,74,76,79,85]. An improved freeze-drying process was used to develop a thermostable Rinderpest vaccine (Thermovax), which was an essential tool for eradicating the disease in remote pastoral areas [127].…”
Section: Summary Of Evidencementioning
confidence: 99%
“…An improved freeze-drying process was used to develop a thermostable Rinderpest vaccine (Thermovax), which was an essential tool for eradicating the disease in remote pastoral areas [127]. In this study we identified dried formulations (freeze-or foam-dried) for vaccines against NDV (e.g., [52]), bovine ephemeral fever virus (BEFV) [74], classical swine fever virus (CSFV) [85], rabies [77], and PPR [47], highlighting that the drying process is a useful technique to improve the thermostability of vaccines against diverse diseases in several species. However, it is worth mentioning that the drying process alone is not able to confer a long-term stability in the formulations.…”
Section: Summary Of Evidencementioning
confidence: 99%
See 1 more Smart Citation